1999
DOI: 10.1080/10430719908404926
|View full text |Cite
|
Sign up to set email alerts
|

The military production function

Abstract: This article analyzes three methods of estimating the military production function which relates military inputs to a measure of military effectiveness. The econometric military production function employs historical data to estimate the relationship between inputs and military effectiveness. A production function estimated during the Vietnam War is provided as an example. The response-surface military production summarizes the input and output data of a large-scale military operations research model. This met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This is not the first paper that attempts to quantify the difference in ability of weapon platforms. The examination of the use of helicopters versus fixed wing aircraft during the Vietnam War by Hildebrandt (1999) estimates a similar value. In that scenario, the weapons were complements whereas in this case, the ships used were substitutes for one another.…”
Section: Introductionmentioning
confidence: 56%
“…This is not the first paper that attempts to quantify the difference in ability of weapon platforms. The examination of the use of helicopters versus fixed wing aircraft during the Vietnam War by Hildebrandt (1999) estimates a similar value. In that scenario, the weapons were complements whereas in this case, the ships used were substitutes for one another.…”
Section: Introductionmentioning
confidence: 56%
“…Typically, such studies have estimated for readily identified measures of effectiveness, such as providing an air defence capability or the numbers of aircraft destroyed or the number of aircraft sorties per day. This approach is used in cost-effectiveness studies but such studies focus on only a limited measure of defence output (Hildebrandt [1990;1999]). For example, a costeffectiveness study of air defence would compare the costs and effectiveness of alternatives such as land-based air defence missiles versus manned fighter aircraft; or anti-submarine capability would compare land-based maritime patrol aircraft versus naval frigates; or anti-tank capability would compare missiles and attack helicopters.…”
Section: The Military Production Functionmentioning
confidence: 99%
“…The interested reader is referred to Hartley and Sandler (2001) and Hildebrandt (1999) for good introductory expositions of these ideas. A good understanding of this literature is critical to the proper evaluation of defence systems.…”
Section: Introductionmentioning
confidence: 99%